Does Influenza Vaccination Modify Influenza Severity? Data on Older Adults Hospitalized With Influenza During the 2012−2013 Season in the United States. (27th March 2015) - Arriola, Carmen S.; Anderson, Evan J.; Baumbach, Joan; Bennett, Nancy; Bohm, Susan; Hill, Mary; Lindegren, Mary Lou; Lung, Krista; Meek, James; Mermel, Elizabeth; Miller, Lisa; Monroe, Maya L.; et al.
Abstract: Background.  Some studies suggest that influenza vaccination might be protective against severe influenza outcomes in vaccinated persons who become infected. We used data from a large surveillance network to further investigate the effect of influenza vaccination on influenza severity in adults aged ≥50 years who were hospitalized with laboratory-confirmed influenza. Methods.  We analyzed influenza vaccination and influenza severity using Influenza Hospitalization Surveillance Network (FluSurv-NET) data for the 2012−2013 influenza season. Intensive care unit (ICU) admission, death, diagnosis of pneumonia, and hospital and ICU lengths of stay served as measures of disease severity. Data were analyzed by multivariable logistic regression, parametric survival models, and propensity score matching (PSM). Results.  Overall, no differences in severity were observed in the multivariable logistic regression model. Using PSM, adults aged 50−64 years (but not other age groups) who were vaccinated against influenza had a shorter length of ICU stay than those who were unvaccinated (hazard ratio for discharge, 1.84; 95% confidence interval, 1.12−3.01). Conclusions.  Our findings show a modest effect of influenza vaccination on disease severity. Analysis of data from seasons with different predominant strains and higher estimates of vaccine effectiveness are needed.